Establishing the Validity and Reliability of the Student Practice Evaluation Form–Revised (SPEF-R) in Occupational Therapy Practice Education: A Rasch Analysis. (March 2016) - Rodger, Sylvia; Chien, Chi-Wen; Turpin, Merrill; Copley, Jodie; Coleman, Allison; Brown, Ted; Caine, Anne-Maree
This study investigated construct validity and internal consistency of the Student Practice Evaluation Form–Revised Edition Package (SPEF-R) which evaluates students' performance on practice education placements. The SPEF-R has 38 items covering eight domains, and each item is rated on a 5-point rating scale. Data from 125 students' final placement evaluations in their final year study were analyzed using the Rasch measurement model. The SPEF-R exhibited satisfactory rating scale performance and unidimensionality across the eight domains, providing construct validity evidence. Only 2 items misfit Rasch model's expectations (both related to students' performance with client groups, which were often rated as not observed). Additionally, the internal consistency of each SPEF-R domain was found to be excellent (Cronbach's α = .86 to .91) and all individual items had reasonable to excellent item-total correlation coefficients. The study results indicate that the SPEF-R can be used with confidence to evaluate students' performance during placements, but continued validation and refinement are required.